The Use of Midjourney in Design Buying and Selling Business from the Perspective of Ibn Ashur's Maqashid Sharia - Hidayat, Febryan; Hanif, Khasnan; Miftakul Janah, Maratus Sholikhah (Universitas Muhammadiyah Surakarta, 2025)
This research is motivated by the rapid development of artificial intelligence (AI) technology across various sectors, particularly in design. One widely used AI tool in design is midjourney. Although AI offers numerous benefits, such as production efficiency and flexibility for non-professional users, its use also raises issues related to design authenticity, third-party utilization, and the potential automation of human roles. Considering the importance of ethical and legal aspects in AI usage, this study aims to examine the role of AI in online design services from the perspective of maqashid syariah according to ibn ashur. This research employs a qualitative approach, specifically a library research method with a phenomenological approach and descriptive analysis techniques, to understand and explain the role of AI within the maqashid syariah framework. The findings reveal that midjourney, as an AI design platform, supports design efficiency and enhances designers’ creativity through text-based automation features. However, its application in commercial design poses copyright challenges, especially when designs are fully generated by AI. From a maqashid syariah perspective, AI in design services aligns with the principle of wealth circulation (Ar-Rawaj) and ownership clarity when using exclusive services. Collaborative use of AI that maintains the active role of designers is deemed more equitable and consistent with maqashid syariah, while excessive dependency may reduce originality.